Study on direct medical cost of inpatient treatment for gastrointestinal cancers at Hue University of Medicine and Pharmacy Hospital - Luu, Nguyen Nguyet Tram; Tran, Xuan Thinh; Tran, Quang Phuc (Tạp chí Y Dược Huế, 2023)
Background: Gastrointestinal cancers, including liver cancer, colorectal cancer, and stomach cancer, are the most common cancers in the world as well as in Vietnam, posing a leading threat to human health. The cost of treating these cancers is a major problem that burdens not only patients but also healthcare systems. The study aims to analyze treatment costs for the four most common types of gastrointestinal cancer nowadays. Materials and method: A cross-sectional study was conducted to collect data from 300 medical records of inpatients with gastrointestinal cancers at the hospital of Hue University of Medicine and Pharmacy in 2021. Results: The average direct medical cost per inpatient admission was 14,239,915 VND (95% CI: 12,502,135 - 15,977,695 VND) in 2021. The cost per inpatient admission for liver cancer treatment was the highest, by 20,267,780 VND (95% CI: 16,036,541- 24,499,018 VND). The cost of drugs accounted for the highest proportion (38.1%), followed by the cost of medical supplies (14.7%). There is a statistically significant difference between the median cost of groups classified by age, metastasis, comorbidity, and length of hospital stay. Conclusion: Direct medical costs for patients with four common types of gastrointestinal cancers impose a considerable economic burden on patients and the health system. Further cost analysis studies need to be conducted. Strategies to decrease the economic burden of gastrointestinal, such as screening programs, and improving awareness of the prevention of cancer should be developed in Vietnam.